O ensino-aprendizagem da autobiografia: uma possibilidade para o desenvolvimento da linguagem escrita - Carvalho, Siberia Regina de (2011)
The main aim of this thesis is to investigate the students language abilities necessary to perform textual production which can be developed through the structured and systematic teaching of the genre autobiography to 5th grade students at a public school. The genre autobiography was chosen as a result of the observation from this researcher of the students interest to tell their life stories and her confidence that it could contribute to the teaching-learning of autobiography, since students might understand their role as subjects of a socio-historic process where language has a singular importance. According to the genre concerned, we discuss Vygotsky s concepts on teaching-learning (1991, 2006) and the conceptualizations on the teaching of genres by Bakhtin (2003), who assumes a dialogic language view, and, also, by Schneuwly (2004), who adopts genre as psychological tool. Furthermore, we discuss the procedures used in the: 1. elaboration of pedagogical materials for the teaching of genres, starting from the processes of pedagogical transposition (CHEVALLARD, 2005); 2. elaboration of the pedagogical model (DOLZ; SCHNEUWLY; HALLER, 2004); and 3. elaboration of the pedagogical sequence (DOLZ; NOVERRAZ; SCHNEUWLY, 2004) of the genre autobiography. Subsequently, we present the texts analysis framework of socio-discursive interactionism (SDI) (BRONCKART, 2003) which guided the elaboration of the model and pedagogical sequence, along with the analysis of texts written by the students, and, lastly, the concept of language capacities (DOLZ; SCHNEUWLY, 2004). Regarding the methodological procedures, our research is based on a socio-historic approach adopting the following steps: 1. procedures for the elaboration of the autobiography model; 2. procedures for the elaboration of the pedagogical sequence of the genre autobiography; 3. analysis of autobiographies written by the students according to this sequence; and 4. presentation of final results. Considering the final result of the analyses, we realized the relevance of working with textual production based on the genre autobiography through many activities organized in a didactic sequence, always observing the features of this genre defined in the model. All procedures employed in this research come from, above all, the SDI as proposed by the research groups Language, Action, Training (LAF), lead by Bronckart (2003, 2006), from the Faculty of Psychology and Sciences of Education at the University of Geneva, and Analysis of Language, Educational Work, and their Connections (Alter), lead by Machado (2008, 2009), from the Graduate Program in Applied Linguistics and Language Studies at the Pontifical Catholic University of Sao Paulo (LAEL/PUC-SP)